Alleviating psoriatic skin inflammation through augmentation of Treg cells via CTLA-4 signaling peptide - Lee, Woo-Sung; Nam, Kyung-Ho; Kim, Jong Hoon; Kim, Won-Ju; Kim, Jeong Eun; Shin, Eui-Cheol; Kim, Gil-Ran; Choi, Je-Min (Frontiers in Immunology, 2023)
Psoriasis is a chronic inflammatory skin disease characterized by hyperplasia of keratinocytes and immune cell infiltration. The IL-17-producing T cells play a key role in psoriasis pathogenesis, while regulatory T (Treg) cells are diminished during psoriatic inflammation. Current psoriasis treatments largely focus on IL-17 and IL-23, however, few studies have explored therapeutic drugs targeting an increase of Treg cells to control immune homeostasis. In this study, we investigated the effects of a cytotoxic T lymphocyte antigen-4 (CTLA-4) signaling peptide (dNP2-ctCTLA-4) in Th17, Tc17, γδ T cells, Treg cells in vitro and a mouse model of psoriasis. Treatment with dNP2-ctCTLA-4 peptide showed a significant reduction of psoriatic skin inflammation with increased Treg cell proportion and reduced IL-17 production by T cells, indicating a potential role in modulating psoriatic skin disease. We compared dNP2-ctCTLA-4 with CTLA-4-Ig and found that only dNP2-ctCTLA-4 ameliorated the psoriasis progression, with increased Treg cells and inhibited IL-17 production from γδ T cells. In vitro experiments using a T cell-antigen presenting cell co-culture system demonstrated the distinct mechanisms of dNP2-ctCTLA-4 compared to CTLA-4-Ig in the induction of Treg cells. These findings highlight the therapeutic potential of dNP2-ctCTLA-4 peptide in psoriasis by augmenting Treg/Teff ratio, offering a new approach to modulating the disease.